Default in The Profit Sharing Agreement Between the State Government and Petuanan Areas - Marselo Valentino Geovani Pariela; Merry Tjoanda; Ronald Fadly Sopamena (Faculty of Law, Universitas Pattimura, 2021)
In Eti Village, which is located in West Seram District, West Seram Regency, an agreement for marine and plantation products sharing is still being carried out between the Petuanan Region and the Eti Village Government as the parent country. The petuanan area or territory is a village or hamlet that is in the territory of the customary village. The agreement for the sharing of marine products and plantations between the Petuanan area and the State Government of Eti Village was agreed to share the profits of marine products and plantations by 40% which would belong to the Eti State Government and 60% to belong to the Petuanan area. This agreement for marine products and plantations is made based on the ngase system. The Ngase system is a form of cooperation between land owners and workers which is carried out at harvest time. However, in practice, this agreement for marine and plantation products does not go according to what has been agreed. The parent country does not get the pre-agreed profit sharing. Petuanan countries do not carry out their obligations to the detriment of the parent country. This study aims to determine the consequences of default in this profit-sharing agreement as well as to examine the settlement of disputes between the Eti Government and the Petuanan area. The type of research used is sociolegal research, which is a combination research method between doctrinal law research methods and empirical legal research methods. The accountability carried out by the petuanan area is the fulfillment of achievements. Settlement of disputes between the petuanan area and the government of Negeri Eti is through non-litigation and litigation channels.